1987
DOI: 10.1007/bf00289400
|View full text |Cite
|
Sign up to set email alerts
|

Growth and body composition changes in mice selected for high post-weaning weight gain on two levels of feeding

Abstract: Two lines of mice were selected for high post-weaning weight gain (3 to 6 weeks) adjusted for 3 week weight. One line (F) was grown on freely available food and the other (S) on a feeding scale set at the same level for all mice. Food intake of the S line averaged 80% of the F line. The realised heritabilities after 6 generations of selection were 0.38±0.06 and 0.33±0.07 for the F and S lines, respectively. In generation 7, mice from the F and S lines and from an unselected control line (C) were compared on bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
3
8
0
Order By: Relevance
“…The heritabilities estimated for weight (Table II) were in the order of those found by N'Drie et al (2007) in poultry and by Lagerkvist et al (1994) and Hansen and Berg (1997) in mink, but larger than those observed by McPhee and Trappett (1987) and Urrutia and Hayes (1988a) in mice and by Cameron (1994), , , and Nguyen and McPhee (2005a, b) in pigs. The reported heritability of 0.19 for animal size in mink (Koivula et al, 2011) is considerably smaller than the above reported heritability estimates for weight in mink.…”
Section: Genetic Parametersmentioning
confidence: 82%
See 1 more Smart Citation
“…The heritabilities estimated for weight (Table II) were in the order of those found by N'Drie et al (2007) in poultry and by Lagerkvist et al (1994) and Hansen and Berg (1997) in mink, but larger than those observed by McPhee and Trappett (1987) and Urrutia and Hayes (1988a) in mice and by Cameron (1994), , , and Nguyen and McPhee (2005a, b) in pigs. The reported heritability of 0.19 for animal size in mink (Koivula et al, 2011) is considerably smaller than the above reported heritability estimates for weight in mink.…”
Section: Genetic Parametersmentioning
confidence: 82%
“…This includes selection for growth, feed intake, or feed conversion ratio on ad libitum (AL) or restricted feeding (RF). Experiments have been performed with mice, pigs, and poultry (Sutherland et al, 1970;Pym & Nicholls, 1979;Hetzel & Nicholas, 1986;McPhee & Trappett, 1987;Cameron, 1994;Nguyen & McPhee, 2005a). Selection for growth on AL feeding is usually associated with increased feed intake and a reduced feed conversion ratio.…”
Section: Introductionmentioning
confidence: 99%
“…If Hammond's (1947) performance testing method, which was a view that the regimen should give fullest modification of one proposed by Kielanowski expression to the trait is accepted, then ad (1968). Evidence in support of this expectation was found in the pig and mouse work of Falconer and Latyszewski (1952), Fowler and Ensminger (1960), Hetzel and Nicholas (1986) and McPhee and Trappett (1987). However, studies on performance test of set duration and food intake.…”
mentioning
confidence: 85%
“…for GR and F respectively. In mouse lines selected for increased body-weight gain on a fixed feeding scale, McPhee, Trappett, Neill and Duncalfe (1980), Hetzel and Nicholas (1986) and McPhee and Trappett (1987) attributed the response to a reduction in the energy used for maintenance and, to a lesser degree, an improvement in the use of retained energy through an increased lean and reduced fat deposition. respectively.…”
Section: Selection Processmentioning
confidence: 99%
“…Selection has been performed for growth on diets differing in quantity, such as ad libitum and restricted feeding (Falconer & Latyszewski 1952; Park et al. 1966; Hetzel & Nicholas 1986; McPhee & Trappett 1987; Urrutia & Hayes 1988), or in quality, such as diluted (Falconer 1960) or low‐protein diets (Park et al. 1966).…”
Section: Introductionmentioning
confidence: 99%